2019
DOI: 10.18517/ijaseit.9.2.8089
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of K-Carrageenan Addition to the Characteristics of Jicama Starch-Based Edible Coating and Its Potential Application on The Grapevine

Abstract: Public awareness of food quality is an essential thing during the packaging application. Considering the environment issue, edible coating with starch-based has been applied as packaging with environment-friendly. The high quality of starch is also produced by jicama (Pachyrhizus erosus). However, the application of jicama as an edible coating for grapevine (Vitis vinira L) remains unknown. Therefore, this research aims to determine the influence of k-carrageenan addition with various concentration to the phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The result of the research shows that the percentage of weight loss of tomatoes with an edible coating which observed for 15 days is lower than the percentage of weight loss of tomatoes without edible coating (Table 1), this shows that the presence of a coating layer based on corn starch containing cinnamon oil serves both as a barrier against CO2, O2, and water which causes respiration and transpiration to be suppressed, so as to maintain fruit quality. Similar results were also revealed by [13] where edible starch-based coatings can inhibit weight loss of the grapevine fruits.…”
Section: Weight Loss (%)supporting
confidence: 84%
“…The result of the research shows that the percentage of weight loss of tomatoes with an edible coating which observed for 15 days is lower than the percentage of weight loss of tomatoes without edible coating (Table 1), this shows that the presence of a coating layer based on corn starch containing cinnamon oil serves both as a barrier against CO2, O2, and water which causes respiration and transpiration to be suppressed, so as to maintain fruit quality. Similar results were also revealed by [13] where edible starch-based coatings can inhibit weight loss of the grapevine fruits.…”
Section: Weight Loss (%)supporting
confidence: 84%
“…Starch-K-carrageenan blends were used in order to develop edible coatings on the grapes. The performances of the coatings/films are dependent on the composition while based on the analyses it can be concluded that the use of these systems can lead to an improved quality of the grapes, namely the vitamin C content is higher while the mass loss is lower (improved barrier properties) but also the sensory evaluation (color and texture) indicates significant improvements, which recommend the use of these blends as edible coating [57].…”
Section: Native Bioactive Polymers As Packaging Materialsmentioning
confidence: 99%
“…Starch is the most widely used as a biopolymer because of the acceptable properties, biodegradability, and thermoplastic properties [1]. Many researchers have IOP Publishing doi:10.1088/1755-1315/1155/1/012014 2 studied polysaccharide-based coatings, including polysaccharide from banana cellulose [2], cactus [3], and soybean [4], various kinds of seeds [5], tapioca [6], jicama [7], sago starch [8]. The edible coating could maintains the quality of commodities such as on banana [9], strawberry [10].…”
Section: Introductionmentioning
confidence: 99%